Implementasi Strategi Knowledge Management Dan Diferensiasi Dalam Upaya Menciptakan Keunggulan Bersaing Pada Sekolah Musik Indonesia - Kresna Raditya (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine how to build a competitive advantage strategy in a music course company with a resource-based theory approach, knowledge management, and differentiation strategies at PT SMI. The research method used is qualitative based on case studies. The results showed that to create a competitive advantage we need to do differentiation and knowledge management strategies. By using a differentiation strategy, SMI is able to create a different value from its competitors, so as to create a competitive advantage